Phosphoric acid doped N-phthaloylchitosan as polymer electrolyte membrane - Yusuf, S.N.F.; Arof, Abdul Kariem; Majid, S.R.; Yahya, R. (2009)
To diversify the applications of chitosan, structural modifications are required. In this work the modified chitosan were synthesized using phthalic anhydride. N-phthaloylation is said to be one of the potential methods to improve the solubility of chitosan in organic solvents. The precipitate obtained after drying in vacuum is yellowish in color and powdery in nature. FTIR proved the occurrence of phthaloylation. 'H NMR spectrum exhibits two sets of broad peaks The FTIR and 'H NMR spectra verified the occurrence of phthaloylation at the amino group of the chitosan. Phthaloyl chitosan shows excellent solubility in organic solvents such as DMF, DMSO, DMAc, and pyridine. The chemically modified chitosan was able to form transparent films by the solvent casting method. Phosphoric acid was introduced as the doping acid at various concentrations from 5 to 25 wt. %. The doped films are also evaluated for its electrical properties using impedance spectroscopy. The maximum conductivity of PhCh film was found to be 2.03 x 10-5 S cm-' exhibited by the film containing 25 wt. % phosphoric acid.